Analisis Persepsi Masyarakat Pesisir terkait COVID-19 di Wilayah Kerja Puskesmas Nambo, Kota Kendari - Sartiya Rini, Dewi; Ruskisnawahuni, Murniati; Astuti, Puji Setya; Irham, I; Musdalifah, M (Health Information : Jurnal Penelitian, 2022)
Kendari City is an area in Southeast Sulawesi Province with the highest number of cases of COVID-19, and one of them occurred in the coastal area of ??Nambo District. The purpose of this study was to determine the perception of the coastal community regarding COVID-19 in the working area of ??the Nambo Health Center, Kendari City. This study used the interview method, and a total of 7 participants. The results of this study indicate that the perception of coastal communities is categorized into psychological and social.